How to write for SCOPUS/ISI-Web of Sciences (WoS) journals : a sharing session - Sahrir, Muhammad Sabri (2016)

(untitled)
Date: 23rd March 2016 Time: 2.00 – 3.30 pm Venue: LR 6, Level 2, IRK Building Organiser: Dept of Fundamental and Inter Disciplinary Studies (FIDS), KIRKHS